The Effect of Accounting Information Systems on the Effectiveness of MSME Accounting Reporting in the Rawa Gebang Market, Langkat Regency - Arnita, Vina; Nurhayati, Siti; Tambunan, Yuliati; Indriani, Yunia (Accounting and Business Journal, 2023)
An accounting information system (AIS) is a set of information components used in accounting activities. The existence of an accounting information system allows the creation of order in the internal organization. This is because AIS makes it easier for human resources (HR) to obtain information related to the organization's economy. This information is utilized in the process of making and determining decisions. System accounting information system (AIS) also has constituent components. These components are the same as the components of the information system, namely, software, hardware, procedures, human resources, and databases. Mahatmayo (2014: 5) explains the components that enable accounting information systems to have important functions, including collecting and storing data about activities. Among them are collecting and storing data about activities carried out, so that management, employees, and databases can be utilized. activities carried out, so that management, employees, and external parties / interested parties can review things that have happened in the organization. Transforming data into information that is useful for management in making decisions in planning, implementing, and monitoring activities. Provide adequate controls to safeguard organizational assets including organizational data, and also to ensure that the data is available when needed accurately, and reliably.